Minimize the Xylitol Production in Saccharomyces cerevisiae by Balancing the Xylose Redox Metabolic Pathway - Zhu, Yixuan; Zhang, Jingtao; Zhu, Lang; Jia, Zefang; Li, Qi; Xiao, Wei; Cao, Limin (Frontiers in Bioengineering and Biotechnology, 2021)
Rational promoter elements engineering approaches were taken in Saccharomyces cerevisiae for efficient xylose fermentation. Among the promoters surveyed, HXT7 exhibited the best performance. The HXT7 promoter is suppressed in the presence of glucose and inducible in the presence of xylose, making it a promising candidate to drive xylose metabolism. However, simple ectopic expression of both key xylose metabolic genes XYL1 and XYL2 by HXT7 resulted in massive accumulation of the xylose metabolic byproduct xylitol. Through the HXT7-driven expression of a reported redox variant, XYL1-K270R, along with optimized expression of XYL2 and the downstream pentose phosphate pathway genes, a balanced xylose metabolism towards ethanol formation was achieved. Within 120 hours of fermentation in a culture medium containing 50 g/L xylose as the sole carbon source, xylose is nearly consumed, with less than 3 g/L xylitol and more than 16 g/L ethanol production. Hence, the combination of a xylose-inducible promoter and redox balance of the xylose utilization pathway is an attractive approach to optimizing fuel production from lignocellulose, which contains abundant xylose.